Deciphering the Water Symbol in T.S. Eliot’s "The Four Quarters" and Ian McMillan’s "Canal Life" - Kamran Zeb; Safaa Falah Hasan; Syeda Aiman Saghir (Al-Qanṭara, 2024)
In this study, the ‘water’ symbol has been deciphered in the poems of T.S. Eliot’s “The Four Quartets” and Ian McMillan’s “Canal Life” and also shed light on their symbolist nature of poetry. The symbol 'Water' has always been considered a prominent literary metaphor because it can represent multiple meanings, such as life, purification, existential reflection, and metamorphosis. It is always open to multiple interpretations. The Four Quartets and Canal Life have explained, interpreted, and illustrated the symbol of 'water' through textual and comparative analyses. A comparative analysis has been conducted to find out the similarities and contrast in the attainment of the ‘water’ symbol in their poems: ‘Canal Life’ by McMillan and ‘The Four Quartets’ by Eliot. It highlights the different ways in which ‘water’ can serve as a symbol in poetry, ranging from a literal representation of community and continuity to a complex metaphor that involves eternal, spiritual, and existential characteristics. The poets demonstrate the many complex and varied characteristics of water as a metaphor, emphasising its ability to provoke a broad spectrum of emotions, thoughts, and introspection within the framework of poetic expression.